Analysis of the Impact of Exports, Taxes, and Exchange Rates on Indonesia’s Economic Growth (2020–2024) - Megawati, Selviana (INCOME: Innovation of Economics and Management, 2025)
The purpose of this study is to determine the impact of exports, taxes, and exchange rates on Indonesia's economic growth. The study used time series data on exports, taxes, and exchange rates for the period from 2020 to 2024. The data analysis methods used included multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results indicate that exports, tax revenues, and the exchange rate have a positive and significant impact on economic growth, both partially and simultaneously. The study concluded that exports, taxes, and exchange rates have a significant positive impact on Indonesia's economic growth. The coefficient of determination analysis shows that exports, taxes, and exchange rates have an impact rate of 50.10% on Indonesia's economic development, while other factors outside the scope of this study account for the remaining 49.90%. For more diverse results, additional macroeconomic variables can also be added which have a greater influence on the analysis of factors influencing Indonesia's economic growth.